2014
DOI: 10.1159/000368219
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Driving Impairments and Associated Cognitive Deficits After Stroke

Abstract: Background: Little is known about the critical on-road driving skills that get affected after a stroke. The purpose of this study was to investigate the key on-road driving impairments and their associated cognitive deficits after a stroke. A second aim was to investigate if lateralization of stroke impacts results of the cognitive and on-road driving tests. Methods: In this cross-sectional study, 99 participants with a first-ever stroke who were actively driving prior to stroke underwent a cognitive battery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
(45 reference statements)
3
20
0
2
Order By: Relevance
“…To fully appreciate the impact of clinical factors identified in this study and others on driving [21,23], on-road driving assessors should be in close communication with the physician. Although our findings may be more clinically relevant to the stroke population seeking a comprehensive fitness-to-drive evaluation than previous studies that used stringent eligibility criteria [8,25,26], there are some limitations inherent to this type of design, including a number of missing data. As the physicians were chosen by the patients, we had no information about the physician's knowledge, experience and attitudes towards fitness-to-drive assessments.…”
Section: Discussionmentioning
confidence: 83%
“…To fully appreciate the impact of clinical factors identified in this study and others on driving [21,23], on-road driving assessors should be in close communication with the physician. Although our findings may be more clinically relevant to the stroke population seeking a comprehensive fitness-to-drive evaluation than previous studies that used stringent eligibility criteria [8,25,26], there are some limitations inherent to this type of design, including a number of missing data. As the physicians were chosen by the patients, we had no information about the physician's knowledge, experience and attitudes towards fitness-to-drive assessments.…”
Section: Discussionmentioning
confidence: 83%
“…Overall, on‐road performance was reported to be significantly decreased in VaD patients: about 70% fail an on‐road test in early disease stages, compared to 11% of healthy drivers. Severe driving difficulties are also reported for patients having experienced a single stroke …”
Section: Discussionmentioning
confidence: 99%
“…There is a need to identify the driving behaviors that are characteristic of various subpopulations of stroke, including various stages (e.g., acute, chronic), severities, and location of stroke. Devos and colleagues [23] aimed to address this by determining whether left and right hemispheric lesions differentially impact on-road driving performance. Although there was no difference in overall score of the on-road test for right and left lesions, results suggested that the lateralization of stroke might influence the aspects of driving that contribute most to the overall driving performance score [23].…”
Section: Discussionmentioning
confidence: 99%